MRI utility in the detection of disease activity in clinically stable patients with multiple sclerosis: a retrospective analysis of a community based cohort. Issue 1 (December 2016) - Cohan, Stanley; Chen, Chiayi; Baraban, Elizabeth; Stuchiner, Tamela; Grote, Lois
Abstract Background Since the application of MRI scanning to the diagnosis and treatment of multiple sclerosis, it has been recognized that only a small fraction of lesions seen on MRI scans produce recognizable symptoms or neurological findings. Because new lesions may occur without clinical detection, the recommendation has been made that MRI scanning be performed on a routine scheduled basis, usually yearly, even in patients who are clinically stable. Methods A retrospective chart review study was conducted on MS patients who had MRI scans of the central nervous system between 2009 and 2012 at Providence Multiple Sclerosis Center. Inclusion criteria were patients with relapsing MS who had been treated with interferon beta or glatiramer acetate for 6 months or longer. Information on type, indication, and result of MRI and whether a change in disease modifying therapy occurred as a result of the scan was collected. Results Of the 436 clinically stable patients who had routine MRI, 16.7 % of subjects had scans revealing new, enlarged or active lesions, yet in only 4.4 % patients was there a change in therapy based upon MRI results. Subjects who had MRI changes were found to be younger (50.15 vs 53.43, p = 0.02) but there was no significant difference in other demographic or clinical characteristics when compared with the subjects who did not have MRI changes. Thirty-six percent of patients with MRI changes did not change DMT due to patient request. Conclusions This study provides data on the likelihood of detecting MRI-documented disease activity, in patients demonstrating longer term sustained clinical stability while receiving DMTs. These results may materially assist in the decision whether or not to perform yearly MRI scanning of such patients. The potential clinical impact of the results of routine MRI scanning must be weighed against the consideration of considerable expense of frequent MRI scanning, and the yet unknown adverse impact of retained gadolinium in patients repeatedly receiving this contrast agent. The long-term clinical impact of not changing DMTs in patients in whom MRI changes were observed will be addressed in future studies of this cohort.